CALIBRATION OF GAFCHROMIC EBT3 FILM FOR DOSIMETRY OF SCANNING PROTON PENCIL BEAM (PBS). Issue 1 (17th January 2018) - Krzempek, D; Mianowska, G; Bassler, N; Stolarczyk, L; Kopeć, R; Sas-Korczyńska, B; Olko, P
Abstract: Gafchromic EBT3 films are applied in proton radiotherapy for 2D dose mapping because they demonstrate spatial resolution well below 1 mm. However, the film response must be corrected in order to reach the accuracy of dose measurements required for the clinical use. The in-house developed AnalyseGafchromic software allows to analyze and correct the measured response using triple channel dose calibration, statistical scan-to-scan fluctuations as well as experimentally determined dose and LET dependence. Finally, the optimized protocol for evaluation of response of Gafchromic EBT3 films was applied to determine 30 × 40 cm 2 dose profiles of the scanning therapy unit at the Cyclotron Centre Bronowice, CCB in Krakow, Poland.